2022
DOI: 10.1107/s2056989022010842
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the azoxy derivative of an antitubercular 8-nitro-1,3-benzothiazin-4-one

Abstract: (Z)-1,2-Bis[4-oxo-2-(piperidin-1-yl)-6-(trifluoromethyl)-4H-benzo[e][1,3]thiazin-8-yl]diazene oxide, C28H24F6N6O3S2, was obtained and its structure determined while attempting to crystallize and structurally characterize 8-nitro-2-(piperidin-1-yl)-6-(trifluoromethyl)-4H-benzo[e][1,3]thiazin-4-one, a simplified analogue of the antituberculosis clinical drug candidate BTZ043. X-ray crystallography revealed the structure of the azoxy compound to be comprised of two benzothiazinone moieties linked by a Z-configure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…18). 66 X-ray crystallography revealed that the structure comprises two BTZ moieties, linked by a Z -configured azoxy group at the C-8 positions in a nearly planar arrangement. The C8–N bond lengths to the azoxy group differ significantly depending on whether the nitrogen atom carries an oxygen atom or not.…”
Section: Reactivitymentioning
confidence: 99%
“…18). 66 X-ray crystallography revealed that the structure comprises two BTZ moieties, linked by a Z -configured azoxy group at the C-8 positions in a nearly planar arrangement. The C8–N bond lengths to the azoxy group differ significantly depending on whether the nitrogen atom carries an oxygen atom or not.…”
Section: Reactivitymentioning
confidence: 99%